The association of temporalis muscle thickness with post-stroke dysphagia based on swallowing kinematic analysis - Kuan-Yu Chen; Shao-Yu Chen; Ming-Yen Hsiao; Tyng-Guey Wang; Meng-Ting Lin (Journal of the Formosan Medical Association)
Background/purpose: Post-stroke dysphagia (PSD) is a common functional deficit after stroke. Temporal muscle thickness (TMT) had been proven to be an independent factor for PSD. However, the relationship between TMT and PSD based on quantitative swallowing kinematic analysis remains unexplored. We aimed to investigate the association between TMT and PSD using videofluoroscopic swallow study (VFSS). Method: We retrospectively recruited stroke patients from May 2015 to March 2020 in the tertiary referral hospital. A total of 83 patients with dysphagia met all the enrollment criteria and were included in the study. TMT was measured by non-contrast brain computed tomography (CT) images. Parameters of VFSS were obtained, including penetration-aspiration scale (PAS), oral transit time (OTT), pharyngeal transit time (PTT) and swallowing trigger time (STT) in four standardized barium formulas respectively. The association between TMT and variables of VFSS were analyzed by adjusted linear and logistic multivariate regression models. Subgroup analysis based on age, sex, and premorbid modified Rankin Scale (mRS) stratification was conducted. Results: TMT was significantly correlated with gender and premorbid mRS as the confounders. Univariate regression showed smaller TMT (p = 0.010) and poorer premorbid mRS (p = 0.018) was associated with prolonged PTT of the thick formula; lesser TMT was associated with prolonged PTT of the paste formula (p = 0.037). Multivariate analyses after confounder-adjustment demonstrated TMT was an independent indicator for PTT in the thick formula (p = 0.028). Conclusion: TMT was associated with swallowing kinematic changes in patients diagnosed with PSD. TMT is an independent indicator for delayed pharyngeal stage in the thick standardized formula during deglutition in PSD patients.